Pre-service Elemenary Teacher Education Curriculum in different States in India A Status Study - Yadav, S.K. (INDIAN EDUCATIONAL REVIEW, 2012)
The study focused on status of implementation of pre-service teacher education curriculum at elementary stage in various states and union territories in India. The major objective was to ascertain the weightage given to different curricular and co-curricular areas and derive implications for action to improve the quality of pre-service teacher education at elementary stage. This study consists of data from 25 states and union territories. The data were collected through mailing questionnaires and personal visits. The descriptive statistical technique was used for analysis of the data. A lot of variations were found in terms of weightage given to different curricular and co-curricular areas.